Analisis Pengaruh ROA (Return On Assets), ROE (Return On Equity), dan EPS (Earning Per Share) terhadap Harga Saham pada Kelompok Industri Barang Konsumsi yang Terdaftar di BEI (Bursa Efek Indonesia) - Sunaryo, Sunaryo (Binus Business Review, 2011)
The primary objective of this research is to learn correlation and effecting among EPS, ROA, and ROE with share price neither partial nor simultaneous. Data secondary collected by industrial samples of consumer groups listed at Indonesian Stock Exchange and the journal preceding research persons. The results of the research describe that EPS has an effecting significant and a high correlation, but ROA and ROE have not any effecting significant and low correlation, but ROA, ROE, and EPS have the effecting significant and high correlation simultaneous to share price. The topic of this research can be continued with other industrial groups or added a lot of new independence variables because if compared to preceding research persons mention the same and differences of its.Â